BOOK REVIEW OF IF I STAY WRITTEN BY GAYLE FORMAN - Meiqal, Radea (LANTERN (Journal on English Language, Culture and Literature), 2013)
The purposes of writing this review are to give comprehension about the art of loving, the power of music, and to give the explanation about the strengths and the weaknesses in If I Stay novel. To develop the comprehension of this review, the writer used library research. Library research is used by collecting the sources through books from library and other sources through internet. Based on the comprehension, the writer found that Mia’s family, Mia’s boyfriend, and Mia’s best friend really love and care to Mia. Besides, music has an important role in Mia’s family. Keywords: Love, Music, Family